Host-Toxin Interactions Involving EspC and Pet, Two Serine Protease Autotransporters of the Enterobacteriaceae - Fernando Navarro-Garcia; Michael Sonnested; Ken Teter (Toxins, 2010)
EspC and Pet are toxins secreted by the diarrheagenic enteropathogenic and enteroaggregative Escherichia coli pathotypes, respectively. Both toxins have a molecular mass around 110 kDa and belong to the same protein family called Serine Protease Autotransporters of the Enterobacteriaceae (SPATE). Furthermore, both toxins act within the cytosol of intoxicated epithelial cells to disrupt the architecture of the actin cytoskeleton. This cytopathic and enterotoxic effect results from toxin cleavage of the actin-binding protein fodrin, although the two toxins recognize different cleavage sites on fodrin. EspC and Pet also have dramatically different mechanisms of entering the target cell which appear dependent upon the E. coli pathotype. In this review, we compare/contrast EspC and Pet in regards to their mode of delivery into the target cell, their effects on fodrin and the actin cytoskeleton, and their possible effects on the physiology of the intestinal epithelial cell.